Thickness effects on magnetic properties and ferromagnetic resonance of Co-Ni-Fe soft magnetic thin films - Kim, YM; Choi, D; Kim, KH; Kim, J; Han, SH; Kim, HJ (ELSEVIER SCIENCE BV, 2003)
In order to apply Co-Ni-Fe thin films for high-frequency magnetic devices, the thickness effects on the magnetic properties of these films have been studied. Coercivity and electrical resistivity of these films increase from 1.5 to 8.9 Oe, and 25 to 88 muOmega cm, respectively, with the decrease of film thickness. The effective permeability of these films is 1300, which is maintained above 700 MHz at 0.1 mum thickness and below. Also, H-k increases from 22 to 65 Oe with the decrease of film thickness, which plays an important role in enhancing the high-frequency characteristics in Co-Ni-Fe thin films with the increase of electrical resistivity. From the XRD, TEM, and FMR investigations of Co-Ni-Fe films, it is certain that the magnetic phases change from amorphous to crystalline phase with the increase of the film thickness. (C) 2002 Elsevier Science B.V. All rights reserved.